Targeting the SR-B1 Receptor as a Gateway for Cancer Therapy and Imaging - Mooberry, Linda K.; Sabnis, Nirupama A.; Panchoo, Marlyn; Nagarajan, Bhavani; Lacko, Andras G. (Frontiers in Pharmacology, 2016)
Malignant tumors display remarkable heterogeneity to the extent that even at the same tissue site different types of cells with varying genetic background may be found. In contrast, a relatively consistent marker the scavenger receptor type B1 (SR-B1) has been found to be consistently over expressed by most tumor cells. In addition, the SR-B1 receptor has been shown to serve as a potential gateway for the delivery of therapeutic agents when reconstituted high density lipoprotein (rHDL) nanoparticles are used for their transport to cancer cells and tumors. Opportunities for the development of new technologies, particularly in the areas of cancer therapy and tumor imaging are discussed.